2003
DOI: 10.1016/j.lts.2003.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor-cleaving protease activity in thrombotic microangiopathy after living donor liver transplantation: A case report

Abstract: Defective plasma activity of Von Willebrand factor (VWF)-cleaving protease (CP) and/or the inhibitors against this protease has been shown to have a pathological role in several forms of thrombotic microangiopathy (TMA). This report describes a patient for whom a diagnosis of TMA was made immediately after living donor liver transplantation. In this patient, activity of VWF-CP and its inhibitor were analyzed serially. At the onset of the disease, VWF-CP activity was quantified as 17%. Inhibitor against this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…It is interesting that several groups have suggested that varying assays of ADAMTS13 activity and inhibitors are useful to predict clinical outcomes of patients who have TMA and are treated with plasma therapy (46,47). Nevertheless, it remains controversial whether a similar mechanism or clinical approach can be valid with patients who develop TMA after solid-organ transplantation, according to case reports that have evaluated this enzyme activity in blood samples of these patients (48,49). Unfavorable responses to PE in this report might be explained by different pathophysiology from deficiency in those factors, but these molecules were not examined in our study.…”
Section: Prognostic Analysesmentioning
confidence: 99%
“…It is interesting that several groups have suggested that varying assays of ADAMTS13 activity and inhibitors are useful to predict clinical outcomes of patients who have TMA and are treated with plasma therapy (46,47). Nevertheless, it remains controversial whether a similar mechanism or clinical approach can be valid with patients who develop TMA after solid-organ transplantation, according to case reports that have evaluated this enzyme activity in blood samples of these patients (48,49). Unfavorable responses to PE in this report might be explained by different pathophysiology from deficiency in those factors, but these molecules were not examined in our study.…”
Section: Prognostic Analysesmentioning
confidence: 99%
“…10 This factor has been proposed to play a major role in the pathogenesis of TMA. Nakazawa et al 15 hypothesized that the severity of the vWF-cleaving protease deficit might be involved in the occurrence of TMA in LDLT recipients because vWF-cleaving protease is exclusively synthesized in the liver and the small-for-size graft in LDLT might have a reduced capacity to produce the enzyme. However, the vWF-cleaving protease level is higher in healthy individuals of blood group O than those of non-O blood groups.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, TMA also can occur in living donor liver transplantation (LDLT) and, to date, there have been sporadic reports of TMA in LDLT recipients. 11,14,15 A total of 106 patients underwent LDLT for various terminal liver diseases at Keio University Hospital (Tokyo, Japan). Of the 106 patients, 4 (3.7%) presented with TMA after LDLT in our institution.…”
mentioning
confidence: 99%
“…29 However, there are reported cases of severe deficiency of ADAMTS-13 activity in lung transplant patients presenting with diffuse alveolar haemorrhage. 30 In our series, ADAMTS-13 activity level was normal in two patients tested.…”
mentioning
confidence: 99%
“…Interpretation of ADAMTS 13 activity following liver transplant may be difficult as it is produced primarily in the liver, and levels may be low in the immediate posttransplant period due to graft ischaemia-reperfusion injury. 29 As such, monitoring of ADAMTS 13 activity should be considered on a case-by-case basis. 31 Serum tacrolimus levels were measured in two cases of tacrolimus-associated TMA following renal transplantation, and no correlation was found between the trough level of tacrolimus and the development of TMA.…”
mentioning
confidence: 99%